2017
DOI: 10.1039/c7ra03897f
|View full text |Cite
|
Sign up to set email alerts
|

Facile single-step bioconjugation of the antifungal agent caspofungin onto material surfaces via an epoxide plasma polymer interlayer

Abstract: We report a facile, one-step, aqueous surface bioconjugation approach for producing an antifungal surface coating that prevents the formation of fungal biofilms. By direct reaction between surface epoxide groups and amine groups on caspofungin, it avoids the use of secondary chemicals. The coating withstands washing with detergent and reduces the growth of the fungal pathogens Candida albicans by log 6 and Candida glabrata by log 3. Importantly, we show that surface adsorption of albumin does not inhibit the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
(4 reference statements)
5
18
0
Order By: Relevance
“…A promissory polymer for antifungal coatings made of allyl glycidyl ether polymerized by plasma treatment was functionalized via the spontaneous reaction between amine and epoxide groups on the surface, as can be seen in Figure 11. Caspofungingrafted polymers were very efficient against the two fungal pathogens C. albicans and C. glabrata; additionally, the materials showed biocompatibility (Michl, Giles, Cross, et al, 2017). More recently, caspofungin has been grafted onto polymethacrylates (Alex et al, 2020) such as poly(2-hydroxyethylmethacrylate) (PHEMA) (Michl, Giles, Mocny, et al, 2017) for antifungal activity against Candida and Aspergillus species.…”
Section: Addition Of Organic-fungicide Compounds To Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…A promissory polymer for antifungal coatings made of allyl glycidyl ether polymerized by plasma treatment was functionalized via the spontaneous reaction between amine and epoxide groups on the surface, as can be seen in Figure 11. Caspofungingrafted polymers were very efficient against the two fungal pathogens C. albicans and C. glabrata; additionally, the materials showed biocompatibility (Michl, Giles, Cross, et al, 2017). More recently, caspofungin has been grafted onto polymethacrylates (Alex et al, 2020) such as poly(2-hydroxyethylmethacrylate) (PHEMA) (Michl, Giles, Mocny, et al, 2017) for antifungal activity against Candida and Aspergillus species.…”
Section: Addition Of Organic-fungicide Compounds To Polymersmentioning
confidence: 99%
“…Covalent immobilization of caspofungin by amine nucleophilic attack to epoxy groups onto polymeric surface (Michl, Giles, Cross, et al, 2017) molecules inside attached by hydrogen bond and other non-covalent interactions. The chemical nature of the pendant groups allows micelle formation, as represented in Figure 12.…”
Section: Drug Delivery Sys Temsmentioning
confidence: 99%
“…Coad et al demonstrated irreversible attachment of the antifungal drug caspofungin using a substrate-independent coating technique which could be applicable to different bulk biomaterials as an essentially two-dimensional surface coating (Coad et al, 2015;Griesser et al, 2015;Michl et al, 2017a). It was shown that using only water or buffer washes was not sufficient in removing the reversibly-bound caspofungin.…”
Section: Grafted Antifungalsmentioning
confidence: 99%
“…The surface coating was also found to have no adverse effects on attachment and growth of mammalian primary fibroblasts (Griesser et al, 2015). Finally, the killing ability of surfaces with attached caspofungin was not diminished even after pre-conditioning the surface with adsorbed layers of protein (Michl et al, 2017a). Kucharikova et al examined caspofungin binding to titanium surfaces (Kucharíková et al, 2015).…”
Section: Grafted Antifungalsmentioning
confidence: 99%
See 1 more Smart Citation